Review of Xenochironomus Kieffer, 1921 (Diptera: Chironomidae) with description of six new species - Fusari, Lívia Maria; Roque, Fabio De Oliveira; Hamada, Neusa (Zootaxa, 2013)
The genus Xenochironomus Kieffer is reviewed. Five new species are described from Brazil, X. alaidae, X. amazonensis and X. martini as male; X. grini and X. mendesi as male, pupa and larva, and X. ethiopensis from Ethiopia is described as adult male. X. canterburyensis (Freeman) is redescribed as male, pupa and larva; X. trochanteratus (Thompson), X. trise-tosus (Kieffer), X. ugandae (Goetghebuer) and X. tuberosus Wang as males; notes on X. xenolabis (Kieffer), X. flaviventris (Kieffer), X. longicrus (Kieffer), X. lacertus Dutta et Chaudhuri and X. ceciliae Roque et Trivinho-Strixino are also given. The species X. nigricaudus Hashimoto is recognized as nomen dubium. Keys to males, pupae and larvae are presented.